Effect of chlorphentermine on the lipids of rat lungs. Issue 5 (October 1976) - Gloster, J; Heath, D; Hasleton, P; Harris, P
Abstract : Chronic administration of chlorphentermine to rats resulted in a reduction of body weight compared to a normal control group. The weight of the heart, liver, kidney, and spleen was less in the treated group while the weight of the lungs was increased significantly. There was no change in the ratio of right ventricular to left ventricular weight in the rats treated with chlorphentermine, supporting the views that this drug does not cause pulmonary hypertension. Biochemical analysis showed that the increase in the weight of the lungs was due to the accumulation of phospholipid. All classes of phospholipid were affected, but particularly phosphatidyl choline, the tissue concentration of which increased nine times. Chlorphentermine also increased the proportion of palmitate present in pulmonary phosphatidyl choline. Histological examination of the lung after treatment with chlorphentermine showed evidence of this drug-induced lipidosis. No conclusion can as yet be reached as to the mechanism involved in the accumulation of phospholipid in the lung after chlorphentermine.